U1 small nuclear RNA chimeric ribozymes with substrate specificity for the Rev pre-mRNA of human immunodeficiency virus. - Michienzi, A (1996)
The in vivo effectiveness of ribozymes strongly depends on the correct choice of the vector molecule. High levels of expression, stability, active conformation, and correct cellular localization are the most important features for a ribozyme vector. We have exploited the utilization of the U1 small nuclear RNA (snRNA) as a vector for specifically targeting a ribozyme into the nucleus. The Rev pre-mRNA of human immunodeficiency virus type 1 was chosen as target for testing the activity of the Ul-ribozyme. The catalytic core of the hammerhead motif, plus the recognition sequences, substituted the stem-loop III of the U1 snRNA. The resulting construct displays efficient cleavage activity in vitro. In addition, in the in vivo system of Xenopus laevis oocytes, the Ul-chimeric ribozyme accumulates in large amounts in the nucleus and produces a considerable reduction of Rev pre-mRNA levels. The Rev-specific ribozyme was also inserted in a derivative of the Ul snRNA mutated in the region of pairing with the 5' splice site, such as to match it with the suboptimal splice junction of the Rev precursor. This construct shows more efficient reduction of Rev pre-mRNA in vivo than the wild-type U1 vector.